Plasmid composition and virulence-associated factors of Yersinia pestis isolates from a plague outbreak at the Paraíba State, Brazil - Leal, Nilma Cintra; Almeida, Alzira Maria Paiva de; Ferreira, Luís Carlos de Souza (Revista do Instituto de Medicina Tropical de São Paulo, 1989)
Pathogenic Yersinia pestis isolates were collected during a plague outbreak at the Paraiba State in 1986. The Y. pestis isolates were investigated for the presence of virulence-associated factors and plasmid content. All strains analysed were proficient in the expression of the VW and fraction 1 antigens, pigment adsorption and pesticin-fibronolysin-coagulase production. A similar plasmid profile composed by four plasmid with molecular weight of 60, 44, 14.9, and 6.4 Megadaltons (MD) was found in all strains. DNA cleavage with EcoRI restriction enzyme further demonstrated the uniform plasmid content of the Y. pestis isolates. Seven additional Y. pestis strains, previously isolated in the same region but in an endemic state, showed the same plasmid fingerprint. The lack of any detectable difference between epidemic and endemic isolates as well as the value of plasmid fingerprints in epidemiology of Y. pestis is discussed.